Rancang Bangun Aplikasi Pengolahan Data Evaluasi Proses Belajar Mengajar berbasis Web pada STIKES Yayasan RS. Dr. SOETOMO SURABAYA. - Setiawan, Permadi; Sulistyowati, Sulistyowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract:Pusat Penjaminan Mutu (PPM) is a unit that is specifically tasked with ensuring quality of service and teaching at Sekolah Tinggi Ilmu Kesehatan (STIKES) Hospital Foundation. Dr. Soetomo. PPM is currently having some problems in data management evaluation of the learning process. One such obstacle is because the data management evaluation of the learning process is still done manually. This causes the management process takes approximately two months, resulting in the evaluation of the learning process to be blocked.Based on these problems made design evaluation data processing applications web-based teaching and learning process that contains the process of making inquiries, the preparation of the questionnaire, questionnaires, and processing questionnaires. In the stage of preparation of this application using SDLC stages watterfall models.The results showed that the application of data processing evaluation learning process can help the STIKES. This is proved by the test results to Kaprodi, lecturers, and student evaluation data processing applications learning process has to meet the needs of each party, as evidenced by the results of experiments conducted to each party declared unfit for use.Keywords: Application, Evaluation, Questionnire